Analysis of cysteine glutathionylation in hemoglobin of gastric cancer patients using nanoflow liquid chromatography/triple‐stage mass spectrometry. (5th February 2020) - Chen, Hauh‐Jyun Candy; Lai, Pang‐Yen; Wu, Deng‐Chyang
Abstract : Glutathione is an intracellular antioxidant capable of scavenging free radicals and detoxifying electrophiles from endogenous and exogenous sources via the free thiol group. Post‐translational glutathionylation at cysteine residues of proteins can affect the structure and cause a functional change of proteins. Protein glutathionylation has been proven to reflect the cellular redox status. Our previous report indicates that the levels of glutathionylation in hemoglobin from peripheral blood of smokers are significantly higher than in nonsmokers. In this study, a nanoflow liquid chromatography/nanospray ionization triple‐stage mass spectrometric (nanoLC/NSI‐MS 3 ) method with a linear ion trap mass spectrometer was employed to quantify glutathionylated peptides in the trypsin digests of hemoglobin from gastric cancer patients. We compare the extent of glutathionylation in hemoglobin from nonsmoking gastric cancer patients with that from nonsmoking healthy adults. Using a carboxymethylated peptide as the reference peptide, the relative quantification of each glutathionylated peptide was measured as the peak area ratio of the modified peptide versus the sum of the peak areas of the modified and the carboxymethylated parent peptide in the selected reaction monitoring chromatograms. Using this method, we found that the extents of glutathionylation at Cys‐104 of the α‐globin and Cys‐93 of β‐globulin hemoglobin from 10 gastric cancer patients were significantly higher than those from 14 normal individuals with p values <0.0001. Our results suggest the possibility of using the extent of cysteine glutathionylation at β‐93 of hemoglobin as an oxidative stress biomarker candidate for gastric cancer.